Regeneration of the Periodontal Apparatus in Aggressive Periodontitis Patients - Zvi Artzi; Shiran Sudri; Ori Platner; Avital Kozlovsky (MDPI AG, 2019)
The purpose of this study is to evaluate and compare, retrospectively, the outcome of two different periodontal regeneration procedures in patients suffering from aggressive periodontitis (AgP). Twenty-eight patients were diagnosed with AgP, suffering from several intra-bony defects (IBD); that were treated by one of two periodontal regeneration techniques randomly assigned to each patient: a. guided tissue regeneration (GTR) or b. an application of extracted enamel matrix derivatives (EMD) combined with demineralized bone xenograft particles (DBX). Probing pocket depth (PPD), clinical attachment level (CAL), and gingival recession were recorded. Pre-treatment and follow-up (up to 10 years from the surgery) recordings were analyzed statistically within and between groups. A significant reduction was shown at time on PPD and CAL values, however, not between subject groups. CAL values decreased in all sites. At the EMD group (44 sites), CAL gain was 1.92 mm (±1.68) from pre-treatment to follow-up (p < 0.001) and at the GTR group (12 sites) CAL gain of 2.27 (±1.82) mm. In conclusion, 1–10 years observations have shown that surgical treatment of AgP patients by either GTR or by application of EMD/DBX results in similar successful clinical results.